Adolescence and Academic Well-being: Parents, Teachers and Students’ Perceptions - Fayyaz, Humera Naz; Hashmi, Kiran (Journal of Education and Educational Development, 2022)
This paper addresses an investigation into the relationship between adolescence and academic well-being. It explores teachers, parents, and students’ perceptions on adolescents’ understanding about emotions and academic development. In adolescence, the students are engaged in both incidental and formal learning, they learn new experiences, and strives to become independent, self-reliant, and confident.  Adolescents prefers to talk more about themselves, their lives, their decisions, their thinking and their ways of approaching solutions.  At this stage, adolescents may get hurt easily, which may lead to dissatisfaction or develop adverse behaviors. These emotional disorders or behaviours need immediate identification by parents, teachers and peers to avoid an effect on their academic performance. Using phenomenological research approach, the study gathered perceptions of teachers, parents and students through three focused group discussions. The data were analysed through thematic analysis techniques. The findings show that there is a relationship between adolescents’ emotions and their academic wellbeing.
Keywords: Adolescence, emotional well-being, academic well-being, self-esteem, and self-confidence